Dall’intenzionalità alla preterintenzionalità. Una riflessione sui sistemi intelligenti - Redaelli, Roberto (Mechane, 2024)
In the debate about the moral standing of artificial intelligence, the question of whether or not technical artefacts have some form of intentionality that would allow them to be considered part of the moral world (or excluded from it) plays a crucial role. The problem of intentionality in fact constitutes a cornerstone in the construction of the notion of moral agency, as demonstrated, among other things, by the fact that technological objects have so far been excluded from the field of ethics because they lack intentionality. In contrast to this exclusion, there is now a trend in the opposite direction, which increasingly attributes some form of intentionality and moral status to AI systems. This paper addresses the clarification of the notion of technological intentionality in artificial intelligence, and especially in generative AI. To this end, it analyses a number of paradigmatic positions in this debate, highlighting their merits and shortcomings. Finally, it proposes replacing the notion of intentionality with the notion of preter-intentionality, which better expresses – according to the thesis put forward – the human-artificial intelligence relationship.